Single‐nucleotide polymorphism, rs1799941 in the Sex Hormone‐Binding Globulin (SHBG) gene, related to both serum testosterone and SHBG levels and the risk of myocardial infarction, type 2 diabetes, cancer and mortality in men: the Tromsø Study. (10th December 2013) - Svartberg, J.; Schirmer, H.; Wilsgaard, T.; Mathiesen, E. B.; Njølstad, I.; Løchen, M.‐L.; Jorde, R.
Summary Low testosterone levels are associated with metabolic and cardiovascular disease risk factor, and have been shown to predict type 2 diabetes mellitus (T2DM), myocardial infarction (MI) and all‐cause mortality. It is not known if these associations are causal or not. Recently, it has been shown that the serum testosterone levels are associated with single‐nucleotide polymorphisms (SNPs), and we therefore studied the associations between one of these SNPs, rs1799941 on the Sex Hormone‐Binding Globulin (SHBG) gene, and MI, T2DM, cancer and death. DNA was prepared from men who participated in the fourth survey of the Tromsø Study in 1994–1995 and who were registered with the endpoints MI, T2DM, cancer or death and a randomly selected control group. For mortality, the observation time was set from 1994, and for the other endpoints from birth. The endpoint data were completed up to 2010–2013. Genetic analyses were successfully performed in 5309 men, of whom 1454 were registered with MI, 638 with T2DM, 1534 with cancer and in 2226 who had died. Men with the minor homozygote genotype had significantly higher levels of total testosterone (14.7%) and SHBG (24.7%) compared with men with the major homozygote genotype, whereas free testosterone levels did not differ significantly between the genotypes. The SNP rs1799941 was not significantly associated with MI, T2DM, cancer or mortality. Thus, our result does not support a causal relationship between total testosterone and SHBG and MI, T2DM, cancer or mortality, suggesting that low testosterone more likely is a marker of poor health.